Diagnosis of commercial plantations of Tectona grandis L. f. in the dry tropics of Michoacan - Muñoz-Flores, H. Jesús; Sáenz-Reyes, J. Trinidad; Barrera-Ramírez, Ruben; Hernández-Ramos, Jonathan; Gómez-Cárdenas , Martín (Ecosistemas y Recursos Agropecuarios, 2022)
To mitigate deforestation in Mexico, commercial forest plantations (FCP) with native and introduced species have been established. The objective was to diagnose the growth, increase and soil of commercial plantations of the introduced species teak (Tectona grandis L. f.), established in the dry tropics of the state of Michoacán. The type of sampling was systematic with intensity between 2.6 and 5.0%. Analysis of variance (ANOVA) indicated significant differences in survival, growth and increments and in the crown, the highest survival values are found in the San Bernardo plantation (Nuevo Urecho municipality) seven years after its establishment, and the largest annual average increments in diameter, height, volume, and cup area, were presented in Las Casitas (Mugica municipality) at three years of age, and no significant differences were found in the plant health status and vigor of the tree.